Implementation of Financing Risk Management in Mudharabah Financing at Bank Mega Syariah Surabaya - Kelvin Ridho Alfarasi; Salsadila Aryanti Adam; Fianelin Widhian Murti; Qasiratuttarfiin Al Natzir (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Financing is one of the products owned by Islamic financial institutions which can help economic growth, the greater the financing provided, the greater the risks involved. Risks that must be considered are financing risks, risks that cannot be handled seriously, and the need for good and appropriate financing risk management to minimize the occurrence of risks that will arise from various activities within Islamic financial institutions. The purpose of this observation is to determine the application of financing risk management in mudharabah financing at Bank Mega Syariah Surabaya. This data collection technique was carried out by interview observation and further analysis then conclusions were drawn. The results of this observation indicate that the Implementation of Risk Management in mudharabah financing at Bank Mega Syariah Surabaya uses 4 stages, namely risk identification, risk measurement, risk monitoring, and risk control. In the risk management process, the risk identification stage in the mudharabah financing process uses the 5C principles which include character, capacity, capital, collateral, and conditions.